Human T-cell leukemia virus type I envelope protein maturation process: requirements for syncytium formation. - Pique, C (1992)
The human T-cell leukemia virus type I (HTLV-I) envelope protein is synthesized as a gp61 precursor product cleaved into two mature proteins, a gp45 exterior protein and a gp20 anchoring the envelope at the cell membrane. Using N-glycosylation inhibitors and site-directed mutagenesis of the potential glycosylation sites, we have studied the HTLV-I envelope intracellular maturation requirements for syncytium formation. We show here that experimental conditions resulting in the absence of precursor cleavage (tunicamycin, monensin treatments, and use of inhibitors of the reticulum steps of the N glycosylations) also result in no cell surface expression of envelope protein. The lack of syncytium formation observed in these cases is thus explained by incorrect intracellular transport. When the precursor is cleaved in the Golgi stack (no treatment or treatment with inhibitors of the Golgi steps of the N glycosylations), it is transported to the cell surface in all the cases examined. Syncytium formation is markedly reduced, however, when Golgi glycosylations are incorrect, which shows that the sugar moieties are involved in the envelope functions. Site-directed mutagenesis demonstrates that each of the five potential glycosylation sites is actually glycosylated. Glycosylation of sites 1 and 5 is required for normal maturation, whereas that of sites 2, 3, and 4 is dispensable. Glycosylation of each site, however, is required for normal syncytium formation. Altogether, the restraints exerted by the cell for the HTLV-I envelope to be transported and functional are very high, which might play a role in the observed conservation of the envelope amino acid sequence between various strains.